Roles and Responsibilities of Notary in Deed Making Agreement on Sale and Purchase Agreement When the Parties Dispute - Irfan Iskhak; Hengki Irawan; Aryani Witasari (Jurnal Akta, 2019)
Notary acts as a medium for the birth of a deed of authentic. Responsibility of notaries in the sale and purchase agreement to the party is limited to deed that made accordance with the authority of his post by UUJN. The purpose of this study are: 1. to know the roles and responsibilities in the making notary deed of sale and purchase agreement in the event of disputes for the parties. 2. To determine the notary solution in preparation of deed sale and purchase agreement in order to avoid disputes of the parties.Based on the results of data analysis concluded that: 1. The responsibility of the notary deed merely on early part deed / deed chief, section final / concluding notarial deed and have full accountability of the contents either formal and material. 2. In the duty of notary shall apply precautionary principle and do legal education in order to avoid disputes in the future.Keywords: Notary; Agreements; Sale and Purchase Agreement; Deed.